Regulatory T Cells Contribute to Sexual Dimorphism in Neonatal Hypoxic-Ischemic Brain Injury. Issue 2 (February 2022) - Beckmann, Lucia; Obst, Stefanie; Labusek, Nicole; Abberger, Hanna; Köster, Christian; Klein-Hitpass, Ludger; Schumann, Sven; Kleinschnitz, Christoph; Hermann, Dirk M.; Felderhoff-Müser, Ursula; Bendix, Ivo; Hansen, Wiebke; et al.
Abstract : Background and Purpose: Neonatal encephalopathy caused by hypoxia-ischemia (HI) is a major cause of death and disability in newborns. Clinical and experimental studies suggest a sexual dimorphism in HI-induced brain injury and therapy responses. A major hallmark of HI pathophysiology is the infiltration of peripheral immune cells into the injured brain. However, the specific role of regulatory T cells (Tregs) in neonatal HI is still unknown. Methods: Nine-day-old mice were exposed to HI by ligation of the right common carotid artery followed by 1 hour hypoxia (10% oxygen). Using immunohistochemistry, flow cytometry, and microarray analyses, Tregs were investigated in the brain, spleen, and blood 24 hours post HI. The functional role of Tregs was evaluated by acute Treg depletion in depletion of regulatory T cells transgenic mice. Brain injury, neuroinflammatory responses, and vascular injury were analyzed via immunohistochemistry and Western blot 48 hours and 7 days after HI. Functional outcome was assessed 3 days and 5 weeks after HI. Results: Female mice revealed an increased cerebral Treg infiltration, coinciding with elevated chemokine receptor expression. Treg depletion in females aggravated HI-induced brain tissue injury, short-term motor deficits, and long-term deficits in exploratory activity, paralleled by an increased microglia and endothelial activation and leukocyte infiltration. Treg depletion in male mice reduced HI-induced brain injury, short-term motor, and long-term cognitive deficits, associated with reduced vascular injury. Ex vivo isolated female Tregs displayed an increased immunosuppressive activity on effector T cell proliferation and an increased gene enrichment in pathways related to enhanced Treg activity. Conclusions: Tregs from neonatal female mice provide endogenous neuroprotection, whereas Tregs from male mice increase secondary neurodegeneration. As potential mechanisms, we identified intrinsic transcriptional differences associated with enhanced anti-inflammatory activity of female Tregs. Our study emphasizes the urgent need for sex-stratified clinical and preclinical analyses. Abstract : Supplemental Digital Content is available in the text.